Design and analysis for an autonomous mobile robots (AMRs) delivery system in smart hospitals - Jiang, Ruoxin (2019)
With healthcare being a manpower strapped industry in Singapore, automation helps to ease the heavy burden and pressure by providing excellent healthcare services. This report aims to find the optimal number of Autonomous Mobile Robots (AMRs) which are used in hospital for improving their current delivery transportation system. The methods used in this paper to achieve the objective included, first, building a queuing model based on the historical data and requirements of the hospital. By setting up this mathematical model, we can convert real cases into an optimization problem. Secondly, computer optimization is subsequently carried out so as to predict the number of robots required to complete all tasks assigned as inputs. It is found that the mathematical model built to be highly representative of the delivery workflow that is to be emulated and from solving the optimization problem, the obtained results is as initially hypothesized. The larger the number of AMRs being used, the shorter the queue time, until it reaches a plateau whereby increasing the AMRs has no effect in reducing the queuing time. Hence, allowing to obtain the optimal number of AMRs at the optimum utilization rate to be used in the hospital to achieve their goal of a Smart Hospital in the near future.